2006
DOI: 10.1002/hyp.6071
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of groundwater use by crop production simulated by DSSAT‐wheat and DSSAT‐maize models in the piedmont region of the North China Plain

Abstract: Abstract:Sustainable water use is in serious crisis in the piedmont region of the Taihang Mountains in the North China Plain, owing to rapid groundwater drawdown. Estimating the water requirement for agriculture, the biggest user of groundwater, will be helpful in understanding groundwater decline. Through the use of DSSAT-3Ð5 wheat and maize models, we assessed water use in winter wheat and maize, two staple crops in the region, in [1987][1988][1989][1990][1991][1992][1993][1994][1995][1996][1997][1998][1999]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 16 publications
(25 reference statements)
2
25
1
1
Order By: Relevance
“…However, the value of P5 was acceptable because study area, cultivar and climate were different (Wang et al, 2012). The kernel number coefficient (G1) was found to be 15 k/g which is closer to value reported by Yang et al (2006) for semiarid climatic conditions in Northern China.…”
Section: Model Calibrationsupporting
confidence: 62%
See 1 more Smart Citation
“…However, the value of P5 was acceptable because study area, cultivar and climate were different (Wang et al, 2012). The kernel number coefficient (G1) was found to be 15 k/g which is closer to value reported by Yang et al (2006) for semiarid climatic conditions in Northern China.…”
Section: Model Calibrationsupporting
confidence: 62%
“…The photoperiod coefficient (P1D) was set to be 60% as reported by Saseendran et al (2004) for semiarid climate of Eastern Colorado. The literature values of grain filling duration (P5) ranged from 332 to 690 GDDo (Saseendran et al, 2004;Nakayama et al, 2006;Yang et al, 2006;Rezzouq et al, 2008;Wang et al, 2012). The P5 value for this study was adjusted to be 650 GDDo.…”
Section: Model Calibrationmentioning
confidence: 99%
“…As 70% of irrigation comes from groundwater, the groundwater table has declined drastically over several decades. According to the report from Yang et al [33], an approximate 100-mm irrigation application in cultivated land leads to about a 640-mm groundwater decline. However, groundwater recharge is not sufficiently met by precipitation.…”
Section: Suggestion For the Sustainability Of Water Resourcesmentioning
confidence: 99%
“…Results of the study indicated, that both, N and water could be reduced by about half of the typical application rates without a strong reduction in yield. Yang et al (2006) used the CERES-Wheat and CERES-Maize models to estimate agricultural water use and its impact on ground water depletion in the piedmont region of the NCP. The results showed a strong correlation between the agricultural water use and the ground water depletion.…”
Section: Case Study China -Model Based Analysis Of a Winter Wheat -Sumentioning
confidence: 99%